A perspective on intermittent fasting and cardiovascular risk in the era of obesity pharmacotherapy - Eliopoulos, Aristides G.; Gkouskou, Kalliopi K.; Tsioufis, Konstantinos; Sanoudou, Despina (Frontiers in Nutrition, 2025)
Intermittent fasting has been linked to metabolic health by improving lipid profiles, reducing body weight, and increasing insulin sensitivity. However, several randomized clinical trials have shown that intermittent fasting is not more effective than standard daily caloric restriction for short-term weight loss or cardiometabolic improvements in patients with obesity. Observational studies also suggest cardiovascular benefits from extended rather than reduced eating windows, and indicate that long-term intermittent fasting regimens may increase the risk of cardiovascular disease mortality. In this perspective, we discuss evidence that may support potential adverse effects of intermittent fasting on cardiovascular health through the loss of lean mass, circadian misalignment and poor dietary choices associated with reward-based eating. Given the ongoing revolution in obesity pharmacotherapy, we argue that future research should integrate anti-obesity medications with dietary strategies that confer robust benefits to cardiometabolic health, combine exercise regimens, and consider genetic factors to personalize obesity treatment. Comprehensive approaches combining diet, pharmacotherapy, and lifestyle modifications will become crucial for managing obesity and minimizing long-term cardiovascular risk.